2022
DOI: 10.1038/s41398-022-02268-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between multimorbidity status and incident dementia: a prospective cohort study of 245,483 participants

Abstract: Multimorbidity (the presence of two or more long-term conditions [LTCs]) was suggested to exacerbate the neuronal injuries. The impact of multimorbidity on dementia has not been fully elucidated. We aimed to investigate the association between multimorbidity and dementia risk. We used the prospective data from 245,483 UK Biobank participants during a 9-year follow-up. Multimorbidity status was evaluated based on the LTC counts and multimorbidity patterns. Cox regression models adjusted for potential confounder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
3
4
0
Order By: Relevance
“…It is worth noting that multimorbidity as a binary entity was not associated with AD, but the increased number of chronic conditions was associated with both AD and VaD. This was in alignment with the report from the UK Biobank Study, 5 , 34 where the load, rather than the presence, of multimorbidity was associated with an increased risk of AD. Furthermore, we had the opportunity to further explore the association of multimorbidity measures with AD‐related plasma biomarkers in a subsample, which showed that the presence of multimorbidity and the number of chronic conditions were associated with increased plasma Aβ42 and NfL, indicating that amyloid and neurodegeneration might partly underline the association of multimorbidity load with dementia.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is worth noting that multimorbidity as a binary entity was not associated with AD, but the increased number of chronic conditions was associated with both AD and VaD. This was in alignment with the report from the UK Biobank Study, 5 , 34 where the load, rather than the presence, of multimorbidity was associated with an increased risk of AD. Furthermore, we had the opportunity to further explore the association of multimorbidity measures with AD‐related plasma biomarkers in a subsample, which showed that the presence of multimorbidity and the number of chronic conditions were associated with increased plasma Aβ42 and NfL, indicating that amyloid and neurodegeneration might partly underline the association of multimorbidity load with dementia.…”
Section: Discussionsupporting
confidence: 82%
“…The population‐based SNAC‐K study in Stockholm, Sweden, found that various patterns of multimorbidity were differentially associated with incident dementia and that certain patterns of multimorbidity (eg, neuropsychiatric, cardiovascular, and sensory impairment/cancer patterns) were linked with an increased risk of dementia 4 . Data from the UK Biobank Study also reported the associations of different multimorbidity patterns (eg, patterns of cardio‐cerebrovascular/respiratory/metabolic/musculoskeletal/depressive disorders and tumor/genitourinary/digestive disorders) with AD and VaD 34 . Our study targeted rural older adults in China, and we generated five multimorbidity clusters (ie, metabolic, cardiac‐MSK, degenerative ocular, respiratory, and mixed clusters).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent population-based registry-based study on comorbidity trends during the last years of life in Finnish patients with dementia aged 70 years or older found an increase in comorbidities between 2001 and 2013 [ 25 ]. Another cohort study of 245,483 participants showed that older adults with multiple comorbid conditions had a higher risk of dementia [ 26 ]. Other factors reported as being relevant include aging, polypharmacy, and a heavier treatment burden, all of which might affect the brain and cause neural injuries [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the main risk factors for dementia are common and frequently coexist, studies 76 typically focus on a single risk factor or a small group of phenotypically similar factors, leaving networks of interactions and synergistic effects unquantified 8 . However, the direct relationships between large numbers of observed traits can be achieved using network analysis.…”
Section: Use Of ML To Understand Modifiable Risk Factors For Dementia...mentioning
confidence: 99%